The effect of Analysis of internal environment in the quality of health care service survey study at AL_Elwiya Maternity Teaching Hospital - احمد يوسف عبد الاله (Journal of Economics and Administrative Sciences, 2013)
he current research aims at showing the correlation and effect of the internal environment analysis in the quality of health service in AL_Elwiya Maternity Teaching Hospital, researcher depended on the integral method in the "analytical descriptive method" for the study of the relation between the main variables and the sub-variables throughout data collection required by the theme of this study, a case study" in tackling the data and information related to the financial aspects of the internal environment. The problem of the study was manifested in the essential question, that is (is there internal structure analysis in the quality of health service). The present study aims at the application of internal structure analysis in the quality of health service. The researcher depended on a number of statistical methods, which are, arithmetic medium, percentile rate, standard deviation to gauge the level of ample agreement and scattering, also such means like Correlation Coefficient, simple linear decline. In order to test the two test the two hypothesis of the study in relation to the effect and the ratio and to diagnose the financial dimension and the reflection of improvement in the quality of health service. The result of study display and analysis showed a number of conclusion the most important relation and the effect of the internal environment in the internal structure analysis in the quality of health service of the sample. The most important of the recommendations is that Al- Elwiya Mat. Hospital should adopt the modern style and apply them in management (TQC, SIC, and the constant improvement). In order to improve the quality of health service in addition to the management of hospital of the sample in the factors of internal structure and its effect of the quality.